EFEKTIFITAS MODEL PEMBELAJARAN PERUBAHAN KONSEPTUAL UNTUK MENGATASI MISKONSEPSI FISIKA PADA SISWA KELAS X SMAN 1 PRAYA BARAT TAHUN PELAJARAN 2012/2013 - Pebrianti, Dwi (Lensa : Jurnal Kependidikan Fisika, 2014)
The aim of this research is to know the influence of problem based learning model assist with interactive simulation to concept comprehension and science generic skill of student. Data analysis used is t-test, by comparing the quarrel of mean from the result of pre-test and post-test. From t-test calculation in concept comprehension and science generic skill, the result is tcount > ttable, it means Ha accepted and Ho failed. In addition, concept comprehension and science generic skill score average in experimental class is higher. So, problem based learning model assist with interactive simulation is better to improve concept comprehension and science generic skill of student.